Mast Cells and Ethanol Consumption: Interactions in the Prostate, Epididymis and Testis of UChB Rats - Mendes, Leonardo O. [UNESP]; Amorim, Joao Paulo A. [UNESP]; Teixeira, Giovana R. [UNESP]; Chuffa, Luiz Gustavo A. [UNESP]; Fioruci, Beatriz Aparecida [UNESP]; Pimentel, Tatiana Aparecida [UNESP]; de Mello, Wilson [UNESP]; Padovani, Carlos Roberto [UNESP]; Pereira, Sergio [UNESP]; Martinez, Marcelo; Pinheiro, Patricia Fernanda F. [UNESP]; Oliani, Sonia Maria [UNESP]; et al. (Wiley-Blackwell, 2011)
ProblemAlcoholism has reached alarming proportions while fertility rates slowing in populations. The assessment of inflammatory effects with emphasis on the variation of the mast cells comparing ethanol chronic ingestion on reproductive organs deserves attention.Method of studyThe mast cells were investigated with light microscopy using toluidine blue to locate and count total mast cells and immunohistochemistry to identify the connective tissue mast cells (CTMC).ResultsThe increase in total mast cells in the prostate, total and degranulated mast cells in epididymis of UChB rats was accompanied by a greater proportion of mucosal mast cells (MMC) in these organs. In addition, a lower incidence of degranulated mast cells was observed in epididymis of control rats.ConclusionsEthanol increases the number of total and degranulated mast cells in the prostate and epididymis, as well as associated with increasing MMC, and therefore, it could be leading to inflammation in these organs.
Keywords: Epididymis; Ethanol; Mast cells; Prostate; Rat; testis